Alternative Resolution of Legal Vacances Guarantee of Aircraft Particularly Aircraft and Helicopters for The Interests Of Creditors In Indonesia - Yuniarto, Efran (International Journal of Business, Law, and Education, 2023)
Since the enactment of Law Number 1 of 2009 concerning Aviation, replacing Law Number 15 of 1992, there has been a legal gap regarding guarantees for airplanes and helicopters in Indonesia, leaving creditors unprotected. While foreign creditors benefit from charges for international interests on aircraft, such as Irrevocable Deregistration and Export Request Authorization (IDERA), domestic creditors are left facing unjust conditions. To address this issue and provide legal certainty for creditors in Indonesia, one alternative is to use the provisions of the material guarantee law, including the use of guaranteed institutions like Fiduciary, and to reconstruct existing laws to allow for the granting of material security rights in the form of mortgages.